Gradual adoption of needle biopsy for breast lesions in a rural state. (9th November 2021) - Murphy, Serena; Yu, Yi‐Chuan; Kerrigan, Colleen; Sprague, Brian; Sowden, Michelle
Abstract: Background: Minimally invasive breast biopsy (MIBB) is the standard of care for the diagnosis of breast cancer, with consensus guidelines suggesting MIBB goals of 90% of total biopsies. In a previous study of patients in the rural state of Vermont, USA (population size of 640, 000), rural breast cancer patients had open biopsies 42% of the time compared to 29% of urban breast cancer patients. The aim of this study was to assess overall population‐based biopsy trends in Vermont. Methods: The Vermont Breast Cancer Surveillance System (VBCSS) was used to identify women receiving MIBB and excisional breast biopsies in Vermont. Patient zip code at the time of initial biopsy was used to determine the patient residence rurality by rural–urban commuting area codes (RUCA 2.0™). Results: There were 9122 diagnostic episodes from 1999 to 2018. MIBB was the initial biopsy method in 7524 (82.5%) cases, while surgical excision was the initial biopsy method in 1598 (17.5%) cases. A linear trend fit estimated an increase of 1.3% per year ( p  < 0.001, 95% CI 1.1%–1.5%) in the fraction of patients undergoing MIBB. Patients living in rural areas were less likely to receive MIBB (78.5%) than those living in urban areas (94.9%), p  < 0.001. Multivariate analysis showed that urban patients and those patients in the years 2014–2018 were more likely to receive MIBB (OR 5.00, 95% CI 4.13–6.05 [ p  < 0.05] and OR 4.41, 95%CI 3.68–5.28 [ p  < 0.05], respectively). The rate of MIBB for rural patients increased and met the 90% quality standard in 2013 and ultimately matched urban patient rates of MIBB in 2018. Conclusions: For the first time, we show that MIBB usage is above 90% in the state of Vermont and that there no longer exist disparities in breast biopsies between urban and rural patients or rural/urban facilities in the state, overall. Abstract : Minimally invasive needle biopsy has been the standard of care for breast cancer diagnosis since the early 2000's. However, a number of studies through 2010, including our prior report from Vermont, showed persistently high rates of open surgical biopsies in rural populations. In this manuscript, we report updated results from a state‐wide retrospective study of breast biopsies, stratified by rurality of patient residence; we evaluated the trend of minimally invasive breast biopsies from 1999 to 2018 and show for the first time that the state as a whole has reached the standard of care of over 90% breast biopsies performed as minimally invasive.